Islamic parents' attitudes and beliefs towards school-based sexual and reproductive health education programmes in Oman. Issue 5 (3rd September 2019) - Al Zaabi, Omar; Heffernan, Margaret; Holroyd, Eleanor; Jackson, Mervyn
ABSTRACT: School-based comprehensive sexuality education (CSE) programmes play an important role in reducing young people's sexual risk behaviour and promoting health and well-being. There is limited evidence regarding the attitudes and beliefs of parents towards the implementation of school-based CSE programmes in Islamic cultural settings, including Oman, which this mixed-method study set out to explore. A convenience sample of 250 parents, with equal numbers of mothers and fathers of children aged 12–14 years (grades 7–9) at two urban public pre-secondary schools in Saham, completed a paper-based self-administered questionnaire in Arabic. We found most parents (72.8%) supported school-based CSE programmes that conformed to Islamic requirements of pre-marital sexual abstinence, but there was some opposition. Almost all parents supported comprehensive age-appropriate CSE being taught to students aged 10–15 years, including topics perceived as controversial in Omani culture, except for birth control and safer sex. Most parents considered themselves, school teachers and school nurses to be important sources of CSE. The study findings which suggest strong parental support for CSE programmes can facilitate education policy, CSE curriculum decision-makers and school healthcare-providers in Oman, other Middle Eastern countries, and countries with Muslim immigrant populations.